Simplifying the Determination of Aggregate Stability Indicators of Mollisols - García, Gisela Vanesa (2020)
Aggregate stability (AS) is a very sensitive soil physical health indicator. The complexity of its determination discourages frequent monitoring. We hypothesized that a reduction of steps to determine AS would yield good AS indicators. We evaluated 196 samples from a range of Mollisols from sandy- to clay-loam surface texture from the southeastern Buenos Aires province, Argentina. Six AS indicators were evaluated: aggregate mean weight diameter (MWD) after capillary wetting (CW) (MWDCW), MWD after sudden immersion in water (VW) (MWDVW), change of MWD (ΔMWD), remnant mass of macroaggregates (MAm) after CW (MAmCW), MAm after VW (MAmVW), and change of MAm between VW and CW (ΔMAmVW-CW). Determining ΔMWD requires six sievings, MWD requires three, ΔMAmVW-CW requires two, and MAm requires only one. Indicators after CW (MWDCW and MAmCW) were not good AS indicators. Likewise, those determined as a difference between CW and VW (ΔMWD and ΔMAmVW-CW) failed to distinguish contrasting AS situations making them unfeasible as universal AS indicators. However, MAmVW explained 99% of MWDVW variability and adequately distinguished among AS situations. With only one sieving, a good indicator of AS could be obtained, and this would encourage the adoption by soil testing laboratories and frequent soil physical health monitoring by farmers.